Kemampuan Keprofesionalan Guru Dalam Menghadapi Kemajuan Teknologi di Era 4.0 - M. Abdillah Khairi; Malik Ubaidillah; Eka Julia Putri; Icha Natasya Aulia; Lilis Astika; Nurul Sufn; Salsabila Yasmin (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
This research is based on as one of the challenges of industry 4.0 in the world of education to build learning innovations carried out by Human Resources (HR). In this case, teachers can take advantage of things such as information technology facilities that are growing rapidly in the era of the industrial revolution 4.0 so that they can play a role in improving the quality of learning. Education is an effort made by the government to produce the nation's children and produce quality human resources. One of the factors for the creation of quality education is the presence of professional teachers. In this case the teacher has the opportunity to develop themselves widely depending on the willingness, desire and readiness to do so. Improving the ability of teachers to carry out their profession should not be too passive, but also proactive, not waiting for opportunities but looking for opportunities. As if the teacher already has such an attitude, then he will always try to develop himself independently in the progress of the times in line with the era of the industrial revolution 4.0. Teachers must be able to master technology to improve the quality of learning and one solution to prepare a competent millennial generation. Therefore, the researchers made SMP IT Al Hijrah 2 Deli Serdang, Medan the object of research to analyze the professional abilities of teachers in using and utilizing technology. Data were collected through qualitative methods, namely by means of observation interviews and documentation. It can be concluded that the teachers of SMP IT Al Hijrah 2 Deli Serdang have mastered and utilized technology effectively and efficiently. Keywords: teacher professionalism, technology, era 4.0.